Lanjar Maibit Oral Literature and Environmental Education: Climate Change Mitigation - Suantoko; Yunita Suryani (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This article aims to provide an alternative environmental education through oral literature. One of the oral literatures that is used as an alternative is the Lanjar Maibit oral literature in Tuban as an effort to mitigate climate change. Based on the dynamic nature of literature, oral literature is able to go beyond the limits of its perspective. Lanjar Maibit oral literature for climate change mitigation. In other words, Lanjar Maibit oral literature is able to discuss the environment as an effort to mitigate climate change in the local area as part of environmental wisdom. The approach used in this article is literary ecological. Data collection methods and techniques use library techniques and field observations based on the type and source of data. Data analysis methods and techniques use Miles and Huberman. The results of the study show that Lanjar Maibit oral literature has environmental education content as an effort to mitigate climate change in the local area. This shows that loving the environment as voiced by Lanjar Maibit oral literature is very important in order to build a harmonious and balanced relationship between the environment and climate change. This kind of relationship can ultimately be used as a breakthrough for climate change mitigation. Oral literature is able to enter into environmental wisdom spaces. Thus, Lanjar Maibit oral literature becomes important as a vehicle for climate change mitigation. Lanjar Maibit oral literature is able to convey messages and move its audience to care about the mitigation of climate change that has occurred recently.